Curcumin in the diet of quail in cold stress improves performance and egg quality - Marchiori M.S.* (2019)
© 2019 Elsevier B.V.Curcumin as a nutritional supplement for animals has been extensively used due to its several pharmacological properties, as antimicrobial, antioxidant, anti-inflammatory, antipyretic and growth promoter. These properties can exert positive effects on poultry health under thermal stress, and consequently, improves egg quality. In this sense, it is known that cold stress exerts negative effects on quail health, which consequently impairs its performance, posture and egg quality. Thus, the aim of this study was to evaluate whether the addition of nanocapsules containing curcumin in the Japanese quail diets could enhance the antioxidant effect of egg yolk and improve the quality indices during thermal stress, as well as to evaluate the performance production. The experiment was randomly performed with four groups (three repetitions with five animals each). The base diet was similar for all animals, and the curcumin (free or nanoencapsulated) was added later, and the groups were divided as follow: T0 (the control group; without curcumin); T30 (supplementation with 30 mg of free curcumin/kg of fed), and T3 and T10 (supplementation with 3 and 10 mg of nanoencapsulated curcumin/kg of feed, respectively). The animals received the experimental diets during 21 days, and the eggs were collected to perform the lipid profile analysis and oxidant/antioxidant status in the last day of experiment (day 21). The addition of curcumin (T30 and T10) improved egg production and reduced feed conversion. The color L (brightness) and b (yellow) were higher in the treatments with curcumin. The levels of thiobarbituric acid reactive substances were lower in the egg yolk of animals from groups T30, T3 and T10 compared to T0. The antioxidant capacity against peroxyl radicals increased in all supplemented groups compared to T0. The saturated fatty acids and polyunsaturated fatty acids levels were lower in the egg yolk of group T10 compared to T0. Finally, the monosaturated fatty acids levels were higher in the egg yolk of groups T10 and T30 compared to T0. Thus, the use of curcumin in the diet of quails exposed to thermal stress improved egg quality. The nanotechnology was able to potentiate the antioxidant effect of curcumin since doses three times lower where used compared to free curcumin, as well as increased the unsaturated fatty acids levels, which can be beneficial to consumer´s health.